First description of the male of the spider tibellus paraguensis Simon, 1897 (araneae: philodromidae), with new distribution records - Achitte Schmutzler, Helga Cecilia (2016)
Fil: Achitte Schmutzler, Helga Cecilia. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.